2022
DOI: 10.7759/cureus.23868
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Colonic Obstruction: Inflammatory Fibroid Polyp

Abstract: Only 5% of all cases of intussusceptions occur in adults. Although it is known to occur frequently due to inflammatory bowel disease, postoperative adhesions, or neoplastic masses, inflammatory fibroid polyps (IFP), which are rare lesions of the gastrointestinal tract, may present this clinical picture. In rare cases of intussusception due to IFP, clinical suspicion should be kept in the foreground and mind in the differential diagnosis. In this article, the purpose was to present the clinical, radiological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Dagistanli et al presented a case of colocolonic intussusception due to a giant lipoma of the transverse colon with good results for the patient. 7 Chiam et al in their clinical case also found that adult-onset colonic intussusception is rare with a reported incidence of 5%, which in turn accounts for only 1-5% of all adult intestinal obstructions. 8 In 90% of cases, an organic pathology is identified as the starting point.…”
Section: Discussionmentioning
confidence: 96%
“…Dagistanli et al presented a case of colocolonic intussusception due to a giant lipoma of the transverse colon with good results for the patient. 7 Chiam et al in their clinical case also found that adult-onset colonic intussusception is rare with a reported incidence of 5%, which in turn accounts for only 1-5% of all adult intestinal obstructions. 8 In 90% of cases, an organic pathology is identified as the starting point.…”
Section: Discussionmentioning
confidence: 96%
“…Tumors are the most common cause of intussusception in adults, and accounts for 63–77% of cases [ 11 ]. Other risk factors include anatomical changes, post-surgical adhesions, fibroids/polyps, inflammatory bowel disease gastrostomy tube and jejunostomy tube [ 12 ].…”
Section: Discussionmentioning
confidence: 99%